A Study on the Effect of Excess Pore Water Pressure on the Deformation of Sheet Pile Wall using PLAXIS 2D - Lian, Yuan Ting; Ling, Felix Ngee Leh (Recent Trends in Civil Engineering and Built Environment, 2021)
Most of coastal area in Malaysia is made up of quaternary deposits, which still undergo consolidating and buildup higher excess pore pressure, increasing the pressure imposed on sheet pile wall. Thus, it emerges the importance to study the effect of excess pore water pressure of retained soil on the deformation of sheet pile wall. The whole workflow was done using PLAXIS 2D 2019. Case study in Muar trial embankment was utilized as base model while parametric study was carried out with proposed row of 6 m long sheet pile wall at the toe of simplified Muar trial embankment model. The findings showed that elevated excess pore water pressure recorded a higher deformation of sheet pile wall. Thus, appropriate type of sheet pile wall must be proposed in order to safeguard the stability of sheet pile wall constructed in unconsolidated soil deposit.